Correlation of clinical and molecular features in myotonic dystrophy type 1 (DM1) - Sedehizadeh, Saam (2019)
Objectives: (1) To correlate RNA splicing misregulation in human DM1 vastus lateralis (VL) muscle of two DM1 splice events identified from the literature and the myotonic dystrophy deep sequencing data repository (nuclear factor I/X (NFIX) and insulin receptor (INSR)), with primary clinical outcome measures. (2) Determine if the clinical outcome measures and these splicing defects changed after 18 months follow-up. (3) Compare differential gene expression in DM1 VL skeletal muscle from patients with a severe phenotype to controls and DM1 patients with a mild phenotype. (4) Establish preliminary proteomic profile of DM1 VL skeletal muscle using mass spectrometry.